Oxygen Saturation of Hemoglobin in Healthy Children of 2- 14 Years at High Altitude in Nepal - Shrestha, S; Shrestha, S; Shrestha, L; Bhandary, N (Kathmandu University Medical Journal, 2012)
Background Individuals residing at higher altitude may have oxygen saturation of hemoglobin different to those living at lower altitude. # Objectives To find out the baseline value of SpO2 in healthy Nepali children (2-14 years) living permanently at high altitude using pulse oximeter and also to study the relation of SpO2 with age, sex and ethnicity. Methods A descriptive observational study was conducted at 4 different altitudes ranging from 2700 to 3800 m in Mustang district. The mean pulse oximery values at different altitudes were calculated and compared. Results One hundred six children were enrolled with the median age of 10 years. The mean SpO2 value of children permanently residing at altitude 2700m was 95.18%, at 2800m was 94.82%, at 3550m was 94.1% and 3800m was 93.1%.The difference in the SpO2 values at different altitude was statistically significant. No sex or age wise differences were noted on the mean SpO2 values in the study group. Conclusions The mean SpO2 values were higher than several other studies done in the altitude above 2500 meters. Enrollment of older children and the different ethnic background could be the contributing factors for the differences. KATHMANDU UNIVERSITY MEDICAL JOURNAL  VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 40-43 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6912